2017
DOI: 10.1249/mss.0000000000001104
|View full text |Cite
|
Sign up to set email alerts
|

Combined Exercise Training Improves Glycemic Control in Adult with Cystic Fibrosis

Abstract: A combined exercise program improves glycemic control in CF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
96
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(103 citation statements)
references
References 28 publications
3
96
4
Order By: Relevance
“…Future studies should also examine which types of exercise training and duration of training that would be optimal to achieve improvements in VO 2 and glucose tolerance as both are desirable outcomes in CF. Overall, the results of our study and Beaudoin et al suggest that improvements in glucose tolerance may be an additional benefit of exercise training. Prospective studies are needed to further evaluate this role of exercise in the management and possible prevention of CFRD similar to what has been demonstrated in gestational and type 2 diabetes …”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…Future studies should also examine which types of exercise training and duration of training that would be optimal to achieve improvements in VO 2 and glucose tolerance as both are desirable outcomes in CF. Overall, the results of our study and Beaudoin et al suggest that improvements in glucose tolerance may be an additional benefit of exercise training. Prospective studies are needed to further evaluate this role of exercise in the management and possible prevention of CFRD similar to what has been demonstrated in gestational and type 2 diabetes …”
Section: Discussionmentioning
confidence: 87%
“…The effect of exercise training on glucose tolerance has been examined in a small study of adult patients with CFRD and abnormal glucose tolerance. Beaudoin et al demonstrated improvement in 2 h plasma glucose values in eight subjects following a 12 week combined strength and aerobic exercise program compared to six control subjects. The exercise group also demonstrated improvements in insulin sensitivity and strength measures, but there was no change in VO 2 or exercise capacity which the authors speculated may be a result of a shorter duration of exercise training.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It also has significant positive benefits in all forms of diabetes. In CFRD exercise has been shown to reduce postprandial glycaemic excursions and total glucose excursions [14]. Therefore, appropriate exercise should be encouraged after the diagnosis of CFRD or dysglycaemia.…”
Section: Exercisementioning
confidence: 99%